2006
DOI: 10.1097/01.pas.0000176427.99004.d7
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Features of Cutaneous Herpes Virus Infections (Herpes Simplex, Herpes Varicella/Zoster)

Abstract: Cutaneous eruptions caused by herpes simplex 1/2 (HSV-1/2) and herpes varicella/zoster (VZV) represent common dermatoses. In some cases, they present with atypical clinical and/or histopathologic features, including presence of dense lymphoid infiltrates with atypical lymphocytes simulating cutaneous lymphomas. In this study, we reviewed the biopsy specimens of 65 patients (33 males, 32 females; mean age, 61.2 years; median age, 62 years; age range, 19-96 years) with cutaneous eruptions caused by HSV-1/2 or VZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 39 publications
(30 reference statements)
1
64
1
4
Order By: Relevance
“…This finding contrasts with studies of infected skin samples from both varicella and herpes zoster, which showed significant numbers of TIA-and granzyme B-expressing cytotoxic T cells (44,51,74). Determination of whether the cytolytic nature of the immune cells observed in this study is the same as that which occurs immediately following natural VZV reactivation (i.e., within the first few days versus the first few months) or whether the CD8 ϩ T-cell response differs depending on tissue factors specific to the skin or sensory ganglia awaits the acquisition and analysis of human ganglia retrieved early in the course of herpes zoster (i.e., the first few days following virus reactivation).…”
contrasting
confidence: 54%
“…This finding contrasts with studies of infected skin samples from both varicella and herpes zoster, which showed significant numbers of TIA-and granzyme B-expressing cytotoxic T cells (44,51,74). Determination of whether the cytolytic nature of the immune cells observed in this study is the same as that which occurs immediately following natural VZV reactivation (i.e., within the first few days versus the first few months) or whether the CD8 ϩ T-cell response differs depending on tissue factors specific to the skin or sensory ganglia awaits the acquisition and analysis of human ganglia retrieved early in the course of herpes zoster (i.e., the first few days following virus reactivation).…”
contrasting
confidence: 54%
“…Mucosal membranes have been shown to contain LC that survey the mucosa for foreign antigens (27), and our hypothesis is that LC present in the respiratory mucosa are the first cells to become infected with VZV and travel to the lymph nodes, where they then infect T lymphocytes with VZV. VZV-infected T lymphocytes then migrate to the skin as part of the inflammatory infiltrate (40,51,58), where they are among the cells responsible for spreading VZV to cutaneous cells. The development of lesions in the typical course of varicella occurs in crops over several days (7), and our findings in the skin of infected patients support the notion that following the initial infiltration of VZV-infected immune cells, cutaneous LC become infected with VZV and emigrate to distal sites, such as draining lymph nodes, to infect additional T lymphocytes that then migrate to the skin to cause additional skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…VZV reactivation results in the production of new infectious virus and a characteristic vesiculopustular rash, which differs from that of varicella insofar as the distribution of the lesions is typically unilateral and covers only 1 to 2 dermatomes (8). In both primary and reactivated VZV infection of human skin, VZV antigens are detectable in the epidermis and dermis (2,30,46,47,49,52), and although some studies have examined the immune infiltrate present in these lesions, most have focused on T lymphocytes, macrophages, and NK cells (40,48,50,51,58). The role of DC subsets in VZV infection in human skin has not been previously explored in vivo.…”
Section: Varicella-zoster Virus (Vzv) Causes Varicella and Herpes Zosmentioning
confidence: 99%
“…9 Histologically, VZV is identical to HSV-1 and HSV-2 ( Figure 3, A and B). 5 Epstein-Barr Virus Epstein-Barr virus causes infectious mononucleosis and is associated with several benign and malignant conditions, including Burkitt lymphoma, nasopharyngeal carcinoma, posttransplant lymphoproliferative disorders, Kikuchi histiocytic necrotizing lymphadenitis, hydroa vacciniforme, Gianotti-Crosti syndrome, and oral hairy leukoplakia. Infectious mononucleosis presents with fever, pharyngitis, lymphadenopathy, and malaise.…”
Section: Clinical and Microscopic Examinationmentioning
confidence: 99%